(untitled) (Journal of Surgical Sciences, 2020)
Pneumothorax and pneumoperitoneum caused by penetrating chest injury are rare. Pneumoperitoneum following trauma usually indicates the presence of a perforated intraabdominal hollow viscous. Other causes of pneumoperitoneum are through the abdominal wall, through the diaphragm, through female genital tract and through retroperitoneum. Here we report an unusual case of pneumothorax and pneumoperitoneum caused by penetrating injury in the posterior aspect of chest in a young male patient of 33 years who presented to us with chest & abdominal pain & breathlessness. The diagnosis was made on clinical & radiological examination. Tube thoracostomy was done followed by laparotomy and repair of diaphragmatic & splenic injury. Post operative recovery was uneventful & the patient was discharged on 9th p.o.d after removal of thoracostomy tube & wound stiches. Journal of Surgical Sciences (2018) Vol. 22 (1) : 67-69